Analysis of borehole water accessibility in Samaru Community, Zaria Metropolis, Kaduna State, Nigeria - Abdulkadir Yahaya Muhammed; Hajara Salahudeen; Adenike Moriliat Saliu; Salamatu Suleiman; Joseph Adeku Maliki; Joseph Mataru Kawai; Imran Hari; Ojeoma Faith Linus (Goodwood Publishing, 2021)
Purpose: This study is aimed at analyzing the water accessibility in Samaru Community, Zaria Metropolis, in Nigeria with a borehole as the center for attraction. Research methodology: Questionnaires, interview, and observation methods were applied in data collection and systematic sampling was adopted in selecting the respondents. The questionnaires were administered from January 2021 to August 2021. Results: The results revealed that the hand pump borehole was the major source of water supply in the study area with 71%. The consumption of water per capita of the majority of respondents, 61%, was less than 30 liters against WHO standards. Then, 59% of respondents cover a distance of between 1-2 km to get access to their water supply. Findings further revealed that cooking use of borehole water was 38% against drinking that is 24%. Additionally, some water-borne diseases like typhoid fever and cholera were reported in some cases. Limitation: The issue at hand virtually affects the whole of the metropolis but eight researchers could not cover all sections because of the limitation of time. Contribution: Research on the provision of clean water and sanitation cannot be overemphasized as they are objective six of the Sustainable Development Goals (SDGs) because of their importance in life.